"It Just Makes You Have More Problems": An Examination of Anti-snitching Codes among Black Youths in Toronto - Haag, Julius (Canadian journal of criminology and criminal justice, 2022)
Subcultural codes against compliance with the police, or "snitching," have factored prominently in public and law enforcement discourses related to urban violence and crime prevention. However, scholarship on these issues focuses almost entirely on the United States. This study investigates attitudes toward compliance with the police and perceptions of snitching among a sample of a Black youths who reside in socially and economically marginalized neighbourhoods in Toronto. Drawing on 32 in-depth interviews, I examine how perceptions of community safety and experiences with policing have impacted young people’s willingness to report crimes and comply with police investigations. Contrary to popular discourses, being seen speaking with police or providing information did not necessarily constitute snitching. Rather, consistent with prior research, a complex set of variables, including age, gender, and the perceived seriousness of the crime, all factored in determining what constituted snitching and when someone was considered a snitch. My findings challenge the essentializing nature of popular discourses on snitching while also highlighting how diminished perceptions of police legitimacy and efficacy have impacted young people’s willingness to report crimes and comply with police investigations. Finally, I discuss the implications of my findings for efforts to reform the police and improve police-community relations.